Realizing precision medicine in chronic lymphocytic leukemia: Remaining challenges and potential opportunities - Stamatopoulos, Kostas; Pavlova, Sarka; Al-Sawaf, Othman; Chatzikonstantinou, Thomas; Karamanidou, Christina; Gaidano, Gianluca; Cymbalista, Florence; Kater, Arnon P; Rawstron, Andy; Scarfò, Lydia; Ghia, Paolo; Rosenquist, Richard (HemaSphere, 2024)
Patients with chronic lymphocytic leukemia (CLL) exhibit diverse clinical outcomes. An expanding array of genetic tests is now employed to facilitate the identification of patients with high-risk disease and inform treatment decisions. These tests encompass molecular cytogenetic analysis, focusing on recurrent chromosomal alterations, particularly del(17p). Additionally, sequencing is utilized to identify TP53 mutations and to determine the somatic hypermutation status of the immunoglobulin heavy variable gene. Concurrently, a swift advancement of targeted treatment has led to the implementation of novel strategies for patients with CLL, including kinase and BCL2 inhibitors. This review explores both current and emerging diagnostic tests aimed at identifying high-risk patients who should benefit from targeted therapies. We outline existing treatment paradigms, emphasizing the importance of matching the right treatment to the right patient beyond genetic stratification, considering the crucial balance between safety and efficacy. We also take into consideration the practical and logistical issues when choosing a management strategy for each individual patient. Furthermore, we delve into the mechanisms underlying therapy resistance and stress the relevance of monitoring measurable residual disease to guide treatment decisions. Finally, we underscore the necessity of aggregating real-world data, adopting a global perspective, and ensuring patient engagement. Taken together, we argue that precision medicine is not the mere application of precision diagnostics and accessibility of precision therapies in CLL but encompasses various aspects of the patient journey (e.g., lifestyle exposures and comorbidities) and their preferences toward achieving true personalized medicine for patients with CLL.